Analisis Faktor Pertumbuhan Laba pada Saat Pandemi Covid-19: Study Kasus Pada Perusahaan Kesehatan - Fenasya Anggrita Densiratu; Murtianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to test and analyze the influence of the Current Ratio, Debt to Equity Ratio, and Net Profit Margin on Profit Growth in the pandemic covid-19: Case Study of Healthy Companies. The quantitative research category encompasses this study. The population studied was health companies listed on the Indonesia Stock Exchange (BEI) throughout the period 2020 to 2022. The sample in this study was 14 companies obtained using the purposive sampling method so that the total data was 42 financial reports. The analysis techniques used are linear regression, classical assumption tests which include normality tests, heteroscedasticity tests, multicollinearity tests and autocorrelation tests, as well as hypothesis testing using the t test. The findings of this research partially show that the Debt to Equity Ratio and Net Profit Margin variables have a significant influence on Profit Growth. Meanwhile, Current Ratio has no significant effect on Profit Growth.